The Subject of the Question of ‘Hidden Fragment’ Suitable for the Lawyers of Hanafi - MAMBETBAYEV, Kairat Zholdubaiuly (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The lawyers of Hanafi School usually say that the hadithes are divided into two fragments: the outer side (zahir) and the inner side (batin). The ‘mursal hadithes’ which occurred in the absence of one or more suppliers of the hadith chain (sanad) belong to the outer fragment. And the hidden fragment (al-Inkitauyil-batin) is determined by the additional conditions which were made to check the content of the hadith. These criteria were produced to make clear the authenticity of the hadith and are a special methodology which is developed by the lawyers of Hanafi. The fundamental studying of this subject is becoming more and more topical for today for deep knowledge of Hanafi school's features. The hidden fragment occurs when the hadith contradicts the stronger data that it is or when the narrator's defect is noticed. In this article, certain conditions which were included by the Hanafian lawyers in order to determine the authenticity of the ahad message and to verify the accuracy of the content of the additional conditions relating to the chain of narration is under consideration.